An Alternative Unifying Measure of Welfare Gains from Risk-Sharing - Auffret, Philippe (World Bank, Washington, DC, 2014)
Following Lucas's (1987) standard approach, welfare gains from international risk-sharing have been measured as the percentage increase in consumption levels that leaves individuals indifferent between, autarky and risk-sharing. The author proposes to measure welfare gains as the increase in consumption growth, instead of consumption levels. When the consumption process is non-stationary, the author's proposed measure has several attractive features: it does not depend on the horizon, and it is robust to alternative specifications of the consumption stochastic processes (from geometric Brownian processes, to Orstein-Ulhenbeck mean-reverting processes), and preferences (from constant relative risk aversion preferences to Kreps-Porteus preferences). The author then uses this measure to estimate potential welfare gains from international risk-sharing for a representative U.S. consumer. The author finds that if international risk-sharing leads only to a complete elimination of aggregate consumption volatility (with no impact on consumption growth), it represents gains to a U.S. consumer of only $ 12 a year on average. But if international risk-sharing also permits an increase in consumption growth, it may have a sizable impact on welfare. Each 0.5 percentage point increase in consumption growth, represents gains to a U.S. consumer of about $ 160 a year on average.